2011
DOI: 10.1002/ase.209
|View full text |Cite
|
Sign up to set email alerts
|

Using embryology screencasts: A useful addition to the student learning experience?

Abstract: Although podcasting has been a well used resource format in the last few years as a way of improving the student learning experience, the inclusion of enhanced audiovisual formats such as screencasts has been less used, despite the advantage that they work well for both visual and auditory learners. This study examines the use of and student reaction to a set of screencasts introduced to accompany embryology lectures within a second year module at Brighton and Sussex Medical School. Five mini-lecture screencas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 23 publications
1
59
1
1
Order By: Relevance
“…Video-watching was associated with better course grades in the study by Romanov [10]. Evans [11] also found that there was data to indicate that screencasts had a positive effect on student outcomes.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Video-watching was associated with better course grades in the study by Romanov [10]. Evans [11] also found that there was data to indicate that screencasts had a positive effect on student outcomes.…”
Section: Discussionmentioning
confidence: 89%
“…Videowatching was also associated with a better course grades. Evans [11] examined student reactions to a set of screencasts introduced to accompany embryology lectures. Five mini-lecture screencasts accompanied by a review quiz were incorporated into a lecture course.…”
Section: Research Backgroundmentioning
confidence: 99%
“…Content was typically selected based on existing curriculum objectives or according to expert recommendations from national organizations (16%). Only 3 studies (7%) commented on the use of multimedia design principles, such as the purposeful design of slide topography to enhance student learning [7][8][9]. …”
Section: Online Lecture Designmentioning
confidence: 99%
“…Regardless of the method of assessment, almost all studies reported high satisfaction and increased knowledge after intervention. Student self-assessment typically revealed positive attitudes toward online lectures as a teaching modality [7,8,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Moreover, students showed increased knowledge in the subject material at hand, as evaluated by pre-and post-lecture knowledge assessment [11,[13][14][15]17,19,21,22,24,25,27,[29][30][31][32].…”
Section: Assessment Of Learning Outcomesmentioning
confidence: 99%
“…There is also a sense of a personal connection with the instructor, which is an important element of the learning process (Evans, 2011).…”
Section: Example 1: Pre-recorded Lectures For 'Flipped Classrooms'mentioning
confidence: 99%